BAKAT ANAK USIA DINI DALAM OLAHRAGA TAEKWONDO MENGGUNAKAN METODE SPORT SEARCH DI KABUPATEN KENDAL TAHUN 2012 (Department of Physical Education, Sport, Health and Recreation, 2012)
AbtrakTujuan dalam penelitian ini adalah untuk mengetahui tingkat kebakatan anak usia dini dalam cabang olahraga beladiri Taekwondo dengan menggunakan metode sport search pada Taekwondoin pra junior di wilayah pengurus cabang Taekwondo Kendal di Kabupaten Kendal tahun 2012. Penelitian yang dilakukan merupakan jenis penelitian kuantitatif dengan populasi Taekwondoin pra junior usia 11-14 tahun diwilayah pengurus cabang Taekwondo Kendal yang berjumlah 360 orang. Teknik pengambilan sampel yang digunakan adalah teknik Area Probability Sampel. Sampel yang diambil sebanyak 108 anak. Instrumen penelitian dengan menggunakan metode sport search. Metode analisis data menggunakan teknik Analisis Deskriptif Persentase. Hasil penelitian menunjukkan tingkat kebakatan anak usia dini dalam cabang olahraga beladiri Taekwondo dengan menggunakan metode sport search pada Taekwondoin pra junior di wilayah pengurus cabang Taekwondo Kendal tahun 2012 adalah kategori berbakat 37,96% (41 anak), dan kategori tidak berbakat sebesar 62, 04% (67 anak). Hal ini dipengaruhi oleh beberapa faktor perbedaan diantara keduanya, yaitu : lama latihan Taekwondo, frekuensi latihan, dan peran orang tua.AbstractTalent level of early childhood in martial sports taekwondo sport using search on pre taekwondoin junior taekwondo in the Kendal branch officials in 2012. Research conducted is a type of quantitative research with a population of around taekwondoin pre juniors ages 11-14 years taekwondo Kendal region of the branch in 2012, amounting to 360 people. The sampling technique used in this study is the random sampling technique. samples taken in this study were 108 children who represent the branch taekwondo Kendal. test instrument used is a sport using search. methods of data analysis using descriptive analysis techniques percentage. Results showed talent early childhood level in martial sports taekwondo sport using pre taekwondoin search on the branch taekwondo junior Kendal in 2012 was category talented 37.96% (41 children), and the categories are not talented at 62.04% (67 children). it is influenced by several factors differences between them, namely the old taekwondo training, exercise frequency, and the role of parents. Based on the above results, it can be concluded that the level of the taekwondoin kebakatan the branch in the taekwondo Kendal most categories showed no talent. although the frequency of less gifted children but if well managed and facilitated by kendal taekwondo will be able to represent at the regional and national levels. based on these conclusions, the researchers gave the following suggestions: 1) the head of the branch of taekwondo kendal to give a special container that is managed and facilitated by the scouting and coaching talents of taekwondoin. 2) for Sebeum nim to provide training and pembinaaprestasi program to explore the potential of the talent that may be owned by the taekwondoin. 3) for taekwondoin should have sincerity in the exercise, and have a desire to continue to explore the potential in martial sports taekwondo.